Death, taxes, and a shotgun wedding - Kelly, Diane (Kelly, Diane. Tara Holloway novel., 2017)
When she begins receiving death threats as she is preparing for her wedding, IRS agent Tara Holloway must sift through past cases to find the culprit, while dodging attempts on her life and tracking down a con artist who is ripping people off for thousands of dollars, before she says "I do."